1999
DOI: 10.1038/sj.bjp.0702327
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ET‐1‐induced contraction of human bronchi by airway epithelium‐dependent nitric oxide release via ETA receptor activation

Abstract: 1 The purpose of this work was to investigate whether endothelin-1 (ET-1) was able to induce the release of an inhibitory factor from the airway epithelium in isolated human bronchi and to identify this mediator as well as the endothelin receptor involved in this phenomenon. 2 In intact bronchi, ET-1 induced a concentration-dependent contraction (7logEC 50 =7.92+0.09, n=18) which was potentiated by epithelium removal (7logEC 50 =8.65+0.11, n=17). BQ-123 , an ET A receptor antagonist, induced a signi®cant leftw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Additionally, ET-1, through interaction with both ET A and ET B receptors, is a mediator of airway tone. ET-1 binding to the ET B receptor promotes bronchial smooth muscle cell contraction, whereas interaction with the ET A receptor promotes NO-induced relaxation [40]. Although ET-1 has been shown to modulate the expression of NO, Markewitz et al [41], using an vitro assay, showed that ET-1, through the ET A receptor pathway, inhibited the activity (approx.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, ET-1, through interaction with both ET A and ET B receptors, is a mediator of airway tone. ET-1 binding to the ET B receptor promotes bronchial smooth muscle cell contraction, whereas interaction with the ET A receptor promotes NO-induced relaxation [40]. Although ET-1 has been shown to modulate the expression of NO, Markewitz et al [41], using an vitro assay, showed that ET-1, through the ET A receptor pathway, inhibited the activity (approx.…”
Section: Discussionmentioning
confidence: 98%
“…Studies in animal and human airways have shown that the epithelial ET A receptor may mediate NO production (via the constitutive NOS) and prostaglandin E 2 production (via the epithelial COX-2) (3,8,31,44). Epithelial NO and prostaglandin E 2 are relaxant for the airway smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial NO and prostaglandin E 2 are relaxant for the airway smooth muscle. In a recent study, Naline and colleagues (44) found that NO is the major determinant of the epithelial regulation of the human airway smooth muscle contraction to ET-1. Our results are in agreement with these authors, because we showed that L-NAME, but not indomethacin and GR-32191, enhanced the contractility to ET-1.…”
Section: Discussionmentioning
confidence: 99%
“…Both ET A and ET B receptors are present on smooth muscle cells of the airways and mediate strong contractions. ET B receptors are present on the airway epithelium as well, where they can induce relaxation through the release of nitric oxide [25] . Asthmatic inflammation causes disruption of the epithelium [26] , which decreases the dilation mediated by ET B receptors.…”
Section: Discussionmentioning
confidence: 99%